2020
DOI: 10.3390/en13020353
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Model Predictive Current-Controlled Permanent Magnet Synchronous Motor Drives with Inaccurate DC Bus Voltage Measurement

Abstract: In this paper, the effects of inaccurate DC bus voltage measurement are analyzed to model predictive current-controlled permanent magnet synchronous motor (PMSM) drives. It is found that the selection of the optimal space vector is affected by inaccurate DC bus voltage measurements, and the shortest distance principle is proposed to evaluate the effects. With the under-voltage measurement, the actual q axis current is always larger than the reference value, and PMSM may be damaged by the over-current phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Over the years, considerable research has been conducted in control engineering, leading to the development of various control techniques aimed at improving system performance, stability, and robustness. Some notable control techniques adopted in the literature include proportional-integral-derivative (PID) control [2], model predictive control (MPC) [3], adaptive control [4], sliding mode control (SMC) [5], fuzzy logic control (FLC) [6], H-infinity control [7] and fractional-order control. Within this array of control techniques, FOC has emerged as a promising and innovative approach that departs from the traditional integer-order control paradigms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the years, considerable research has been conducted in control engineering, leading to the development of various control techniques aimed at improving system performance, stability, and robustness. Some notable control techniques adopted in the literature include proportional-integral-derivative (PID) control [2], model predictive control (MPC) [3], adaptive control [4], sliding mode control (SMC) [5], fuzzy logic control (FLC) [6], H-infinity control [7] and fractional-order control. Within this array of control techniques, FOC has emerged as a promising and innovative approach that departs from the traditional integer-order control paradigms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in engineering practice, it is found that when the combined power supply system operates normally, a sudden change in the servo system load will cause undervoltage, overvoltage and harmonic oscillation to the bus voltage, which will, in turn, cause the system's power supply voltage to be unstable and affect the normal operation of the system [9]- [11]. Some scholars have studied and analyzed the influence of power supply quality on electrical equipment.…”
Section: Introductionmentioning
confidence: 99%